RESOURCES DEVELOPMENT MANAGEMENT OF STUDENT COOPERATIVE MEMBERS IN IMPROVING THE HEALTH OF THE MALANG STIEKTOP COOPERATIVE - Budi Iriani Yudaningrum (STIEKOP MALANG PRESS, 2022)
Purpose – This research aimed to find out how the role of the Human Resources Cooperative, which focused on the roles of managers, employees, and members of the Cooperative Employees, students, changed over time. Design/methodology/approach – The research method used in this research is descriptive qualitative. The process of data collection is done by observation, interviews, and documentation. Results from the study showed the role of managers in cooperative employees of students. Findings – Results from the study showed the role of managers in cooperative Students' employees are; (a) to create an operational policy approved by the board; (b) to manage capital and assets owned by cooperatives; (c) to maintain communication with cooperative members and employees below; and (d) monitor and assess the performance of employees cooperatives. While employees' roles in the cooperative are: (a) competent in the work performed; (b) effective communication skills; (c) decency in cooperative interactions; and (d) understanding the needs of cooperative members. Then the roles of cooperative members are: (a) fulfill all obligations and settle all payments to cooperatives, and (b) abide by the majority decision or comply with the decision resulting from the Annual Member Meeting. Research limitations/implications – This result cannot be obtained by using this method of research in STIEKOP Malang and using time. Originality/value – From this research, This is due to a weak managerial cooperative and the appendices that support the decreasing score of the health cooperative assessment are not well documented. Suggestions relating to this study include that the cooperative employees of students should constantly train and educate the employees and members of the cooperative employees of students. Keywords: Cooperative, Human Resource, Development Paper type: Case Study